A study on the KTM komuter’s customer service performance provided by the tele-marketeer team / Norzatulcima Jamaluddin - Jamaluddin, Norzatulcima (1996)
KTM Komuter is the most ambitious project ever handled by KTMB with a vision to propel the railway industry into a new era of modernization . Modernization of rail transport infrastructure will contribute to the economic development of Klang Valley’s population which goes in line with the Government’s vision in achieving a developed nations by the year 2020 . The study area will try to analyse the Commuter Service Department’s marketing strategy with the main focus on the hotline services called the 'Commuter Connection’ . The Commuter Connection Services is a marketing tools to improved customer service standard with the help of Tele-marketeer Team . A survey was made by distributing structured questionnaires among commuters and households to analyse the effectiveness of the Commuter Connection Services . The data were analyse using table of forms showing their percentage level . Informal interviews and general observations were also done to seek any problems faced by the study area .